Implementation of Innovation Development Means for the Economical Expansion of Enterprises - Miečinskas, Aldas; Miečinskienė, Algita (Ekonomika, 2003)
Making more active of innovations in enterprises is a perspective economical development possibility for transformed or developing countries to expend their economy. In this article is evaluating the innovation activity of Lithuania enterprises. Furthermore the possibilities of innovations making more active in the enterprises are analysed, classified and evaluated.